Dermatological adverse drug reactions with particular reference to Steven-Johnson syndrome and toxic epidermal necrolysis - Banday, Muddasir Sharief; Rather, Sajad Ahmad; Mufti, Samina; Qureshi, Sabia (Asian Journal of Medical Sciences, 2023)
Background: Drug therapy is an inevitable cause of cutaneous adverse reactions. Aims and Objectives: The primary aim was to identify the incidence and magnitude of various dermatological adverse reactions including Steven-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). Moreover, secondary aim was to quantify the risks associated with the use of specific medications. Materials and Methods: A prospective and hospital-based study was conducted in the department of dermatology SMHS hospital on hospitalized cases of cutaneous adverse drug reactions (CADRs). Informed consent was sought and reactions were reported on validated questionnaire based on adverse drug reaction (ADR) monitoring form provided by Central Drug Standard Control organization Ministry of Health and Family Welfare, Government of India. These dermatological reactions were assessed for the clinical pattern, causative agents, and prognosis. The WHO-Uppsala Monitoring centre system for standardized case was used for causality assessment of all cases identified. Results: A total of 101 hospitalized patients with varied dermatological ADRs were reported during the study period. Cases were found more in females (n=75, 74.25%) than in males (n=26, 25.75%). CADRs that were reported in our study were exanthematous rash, fixed drug eruptions, urticarial rashes, SJS, TEN, urticarial vasculitis, anticonvulsant hypersensitivity syndrome, erythema multiforme, contact dermatitis, exfoliative dermatitis, mucosal hyperpigmentation, and nail pigmentation, respectively. After a meticulous drug history, the drugs implicated in causing the cutaneous reactions were anticonvalscents such as phenytoin, carbamazepine, lamotrigine, and phenobarbitone. Other drugs identified were non-steroidal anti-inflammatory drugs such as oxicam, antibiotics such as sulfasalazine, cefixime, cefpodoxime, amoxicillin, fluoroquinolones such as levofloxacin and ciprofloxacin, chemotherapeutic agents such as cyclophosphamide, 5FU, and hydroxurea. Conclusion: The present study concluded that skin is most common target for ADRs. Drug-induced cutaneous reactions can be as simple as a mild rash to rare life-threatening SJS and TEN. Moreover, certain group of patients is at increased risk for developing CADR’s as women are more susceptible than men.